Reaksi Pasar Modal Dengan Adanya Stock Split Saham Pada Perusahaan Go Public Periode Tahun 2008-2011 - Wisnu Pamenang; Harlen dro (Jurnal Ilmiah Mahasiswa FEB, 2012)
The background of this research aims to determine whether there is a significant market reaction to stock prices, abnormal stock returns and trading wolume between stock split events surrounding the period ie the period before, during and  after the stock split at the company went public on the Stock Exchange in 2008-2011.This research is a study which belong to the category of event study or study events. Event study is research that studies the market reaction to an event (event) that the  information is published as an announcement.This study used a sample of 21 companies that perform stock split policy in the period 2008-2011. Test this hypothesis using a different test that is paired sample t-tests on all the variables: stock price, abnormal stock returns and trading volume. Difference test was conducted with a 95% confidence level. Results of this study indicate that the overall market's response to the stock split, this is indicated by the presence of significant differences in all variables (stock price, abnormal stock returns and trading volume).Keywords: Stock Split, Stock Price, Abnormal Return, Trading Volume Activity